(NtRUDY (B3-(NGO wSESO@ZNOGO SOWE]ANIQ PO LAWINAM(B, (NkIROWSK SENTQBRX (B1986 (NG(B. /s - (NwSESO@ZNOE SOWE]ANIE PO LAWINAMs ((NlENINGRAD (B:s (NgIDROMETEOIZDAT(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE DOKL(B.s
Keywords: (NsNEVNYE LAWINYs